2016
DOI: 10.1515/ijamh-2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

Physical self-esteem and personality traits in Swedish physically inactive female high school students: an intervention study

Abstract: A 6-month physical activity program can positively influence physical self-esteem and the frequency of physical activity, both from a short- and long-term perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…An aspect that could be investigated in future research is the precise mechanism that leads to high intercorrelations between personality traits, physical self-worth, and physical activity. Kahlin et al (2016), for example, found small associations between personality factors and compliance with a sports program that enhanced physical self-worth. One could argue that higher Conscientiousness, for example, leads to higher physical activity (Wilson & Dishman, 2015), which leads to higher physical self-worth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An aspect that could be investigated in future research is the precise mechanism that leads to high intercorrelations between personality traits, physical self-worth, and physical activity. Kahlin et al (2016), for example, found small associations between personality factors and compliance with a sports program that enhanced physical self-worth. One could argue that higher Conscientiousness, for example, leads to higher physical activity (Wilson & Dishman, 2015), which leads to higher physical self-worth.…”
Section: Discussionmentioning
confidence: 99%
“…Sonstroem et al (1994), for example, discovered a positive effect of exercise on self-esteem in adults, and another study showed the same pattern in children (Ekeland et al, 2004). An intervention study in Sweden showed that exercise had a positive short-term and long-term influence on physical self-perception (Kahlin et al, 2016). Furthermore, a randomized controlled trial that involved participants in a 6-month exercise program showed a positive effect on general self-esteem and an even bigger effect on the four subdomains of physical self-worth (McAuley et al, 2000), as proposed by Harter (1985).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Studies have also shown that physical activities could be one factor for achieving academic goals and increasing the general wellbeing of adolescents [ 3 , 6 , 7 , 8 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Additionally, authors have shown that a regular physical activity over several weeks has positive effects on the executive functions and academic performance of preadolescent children [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regular and adequate training since childhood should not only lead to the development of fitness and motor performance, but also to the development of a series of personal traits of the individual ( Kahlin et al., 2016 ; Joyner & Loprinzi, 2018 ). Many of those personal traits are considered to be the predictor for adherence to physical activity ( Annesi, 2004 ).…”
Section: Introductionmentioning
confidence: 99%